Bilingual Counseling Students Developing Cultural and Language Competence in Mexico - Claudia G Interiano-Shiverdecker; Derek Robertson; Sofia Santillan; Mica Stumpf (Teaching and Supervision in Counseling, 2023)
Scholars have recently called for a greater research focus on bilingual counselor education and training. This study aims to explore the impact and development of study abroad immersion experiences on Latine bilingual counseling students. This study used transcendental phenomenological research to explore the lived experiences of bilingual counselors (N = 7) during a two-week study abroad program in Oaxaca. Participants comprised master’s and doctoral level students at a CACREP-accredited program who identified as Latine, Spanish-speakers. Through individual interviews, we discovered three themes from the data: (a) personal and professional connection to the study abroad program, (b) developing cultural competence through introspection, self-awareness, and humility, and (c) increasing professional Spanish while embracing nuances. Latine, Spanish-speaking reported growth in their linguistic abilities, self-understanding, and knowledge of Latine cultures. We discuss implications for counselor education study abroad pedagogy and research, as well as how study abroad can promote competence for bilingual counselors.
Keywords: bilingual counselors; study abroad; language competence; cultural competence; Latinx